Cost-effectiveness of workplace wellness to prevent cardiovascular events among U.S. firefighters. Issue 1 (December 2016) - Patterson, P.; Smith, Kenneth; Hostler, David
Abstract Background The leading cause of death among firefighters in the United States (U.S.) is cardiovascular events (CVEs) such as sudden cardiac arrest and myocardial infarction. This study compared the cost-effectiveness of three strategies to prevent CVEs among firefighters. Methods We used a cost-effectiveness analysis model with published observational and clinical data, and cost quotes for physiologic monitoring devices to determine the cost-effectiveness of three CVE prevention strategies. We adopted the fire department administrator perspective and varied parameter estimates in one-way and two-way sensitivity analyses. Results A wellness-fitness program prevented 10% of CVEs, for an event rate of 0.9% at $1440 over 10-years, or an incremental cost-effectiveness ratio of $1.44 million per CVE prevented compared to no program. In one-way sensitivity analyses, monitoring was favored if costs were < $116/year. In two-way sensitivity analyses, monitoring was not favored if cost was ≥ $399/year. A wellness-fitness program was not favored if its preventive relative risk was >0.928. Conclusions Wellness-fitness programs may be a cost-effective solution to preventing CVE among firefighters compared to real-time physiologic monitoring or doing nothing.